Characteristics and densification mechanisms of shallow oil in Chengbei Terrace Area. (17th April 2016) - Wu, Z.; Zha, M.; Gao, C.; Xu, S.; Qu, J.; Wu, Y.
ABSTRACT: Shallow oil is gaining more and more attentions worldwide due to its low cost. However, it is easy to form heavy oil in shallow layers. The wide varieties of oil make research on this subject difficult and oil densification mechanisms are usually controversial. Therefore, the geochemical characteristics of both heavy and light oil in shallow layers are compared and studied comprehensively. Research is conducted on the physical properties, group compositions, and diverse biomarkers. Most shallow oil samples exhibit high densities and low freezing points, which show low-sulfur biodegradation environment. With respect to group compositions, asphalts are more prevalent in the sag center. At different oil densification stages, tricyclic and tetracyclic terpanes are found to increase when viscosity is more than 1000 cp, and decrease when viscosity is less than 1000 cp. Pr/nC17 has similar characteristics. The changes in the contents of n-alkanes and tricyclic terpanes are found to be diametrically opposed when the oil viscosity increases. Underground water and fault systems are found to be the most important factors of oil densification in shallow oil reservoirs. The research on the geochemical characteristics of shallow oil is important to find better development methods and to select high-quality oil.